Анималистическое искусство кобанской культуры и скифо-сибирский звериный стиль - Вольная (Керцева), Г.Н. (Археологія і давня історія України, 2019)
Статья посвящена взаимовлиянию и взаимопроникновению кобанского анималистического искусства и скифо-сибирского звериного стиля, которые во многом основываются на культуре центрально-европейского искусства предскифского периода, ближневосточного, и урартского искусства. The Koban animalistic art and the Scythian-Siberian animal style in many respects are based on culture of the Central European art of the pre-Scythian period, Middle East and Urartu art. In some cases, both directions use similar compositions (whirlwind forms and symmetric), the same animal images («the scraped predator», a winged predator, a deer, a ram, a goat, the head and a figure of the flying bird of prey, fish), and parts of animals (a boar canine teeth) who receive various art interpretation. In the Koban animal style there was an infiltration of images of the Scythian-Siberian animal style (figures of deer with the head turned back and the turned-in legs; animals with the turnedout back part of a trunk at an angle 180°; the predator which was curtailed in a ball), occurs registration of the Koban bronze trapezoid zone buckles Scythian motives). Also the return process of penetration of the Koban images into Scythian art is known (objects in the form of a bust of a bird of prey, «the scraped predator»). All this demonstrates difficult centuries-old interaction of two directions of animal art.